Deficits in Emotion Regulation Partly Mediate the Relation Between Sleep Problems and Depressive Symptoms in Adolescent Inpatients With Depression - Kirschbaum-Lesch, Inken; Holtmann, Martin; Legenbauer, Tanja (Frontiers in Psychiatry, 2021)
Sleep problems are a risk factor for the development of depressive disorders and influence the severity and treatment of depressive symptoms negatively. To enhance treatment for depression in young people, it is important to advance the understanding of the relationship between sleep problems and depressive symptoms. Since deficits in emotion regulation are discussed as possible underlying mechanisms, the present study investigated the mediating effect of maladaptive and adaptive strategies for emotion regulation on the association between sleep problems and depressive symptoms. Emotion regulation strategies, depression and sleep quality were assessed via self-report in a large clinical sample of 602 adolescents (age 13 to 18 years) who reported clinically relevant symptoms of depression. The questionnaires were assessed at admission for inpatient psychiatric treatment. Correlation and mediation analyses were performed. There was a significant partial mediation effect (β = .554, p <.001, R2 = .527), indicating that sleep problems influenced depressive symptoms via the decreased use of adaptive strategies and the increased use of maladaptive strategies. Additionally, a direct effect of sleep problems on depressive symptoms emerged (β = .251, p < .001, R2 = .364). This cross-sectional study provides first indications that additional treatment modules focusing on sleep and ER skills in prevention and treatment programs for adolescents would be important steps. Longitudinal studies are needed to substantiate these results.